2016
DOI: 10.1073/pnas.1524857113
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced gene expression and behavior are controlled by DNA methylation and methyl donor availability in the dentate gyrus

Abstract: Stressful events evoke long-term changes in behavioral responses; however, the underlying mechanisms in the brain are not well understood. Previous work has shown that epigenetic changes and immediate-early gene (IEG) induction in stress-activated dentate gyrus (DG) granule neurons play a crucial role in these behavioral responses. Here, we show that an acute stressful challenge [i.e., forced swimming (FS)] results in DNA demethylation at specific CpG (5′-cytosine-phosphateguanine-3′) sites close to the c-Fos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
94
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 46 publications
6
94
1
1
Order By: Relevance
“…We found, serendipitously, that forced swimming raises histone H3 phosphorylation (H3S10p) selectively in sparsely distributed, mature dentate granule neurons in rats and mice [26,27]. It appeared that this histone mark exists in combination with an acetylation mark at lysine14 (i.e., H3S10p-K14ac; and lysine9 H3K9ac-S10p; [12]), indicating that this combinatorial epigenetic mark could be involved in transcriptional activation [27,28]. Subsequent studies showed that the formation of H3S10p-K14ac in DG neurons was dependent on signaling through GRs and NMDA-Rs [13,27,28].…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…We found, serendipitously, that forced swimming raises histone H3 phosphorylation (H3S10p) selectively in sparsely distributed, mature dentate granule neurons in rats and mice [26,27]. It appeared that this histone mark exists in combination with an acetylation mark at lysine14 (i.e., H3S10p-K14ac; and lysine9 H3K9ac-S10p; [12]), indicating that this combinatorial epigenetic mark could be involved in transcriptional activation [27,28]. Subsequent studies showed that the formation of H3S10p-K14ac in DG neurons was dependent on signaling through GRs and NMDA-Rs [13,27,28].…”
Section: Introductionmentioning
confidence: 86%
“…Hence, pre-treatment with SAM before forced swimming resulted in an increased DNA methylation of the gene promoters/5 -UTR of Fos and Egr1 and decreased expression of these IEGs specifically within the DG. SAM administration also interfered with the memory consolidation process post-forced swimming, because the rats presented significantly less behavioral immobility than the vehicle-treated animals during the FS re-test 24 h later [12]. Importantly, SAM exerted no effects on the forced swimming-induced formation of H3S10p-K14ac in DG neurons; thus, the methyl donor did not affect the FS-activated signaling pathway required for IEG induction in these neurons [12].…”
Section: Histone and Dna Methylationmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that T. gondii is able to co-op host mechanisms of chromatin regulation. Advances in epigenetics have demonstrated that DNA methylation within cells is not as restricted to development as it was once considered; DNA methylation is a dynamic process [94][95][96]. Epigenetic modifications are essential for neurological functions such as memory, hormonal, and behavioral responses.…”
Section: Epigenetic Changesmentioning
confidence: 99%